Evaluating the energy and economic performance of hybrid photovoltaic thermal system integrated with multiwalled carbon nanotubes enhanced phase change material - Rajamony R.K.; Pandey A.K.; Sofiah A.G.N.; Paw J.K.S.; Periyasami G.; Chopra K.; Chinnasamy S.; Farade R.A. (Elsevier Ltd, 2025)
Photovoltaic thermal (PVT) systems represent an advanced evolution of traditional photovoltaic (PV) modules designed to generate electrical and thermal energy simultaneously. However, achieving optimal and commercially viable performance from these systems remains challenging. To overcome this issue, in this research, multiwalled carbon nanotube (MWCNT) enhanced phase change materials (PCMs) integrated with PVT system to enhance electrical and thermal performance has been studied. An experimental investigation with three different configurations, PVT, PCM integrated PVT (PVTPCM), and MWCNT enhanced PCM integrated PVT (PVTNePCM) systems, was carried out under varying solar radiations and a water flow rate of 0.013?0.016 kg/s compared to conventional PV system. A two-step technique was employed to formulate the nanocomposites, and the energy performance of both PV and PVT systems assessed experimentally. The performance of PVTPCM and PVTNePCM systems was evaluated using the TRNSYS simulation technique. The formulated nanocomposite exhibited a 71.43% enhancement in thermal conductivity, a significant reduction in transmittance up to 92% and remained chemically and thermally stable. Integration of NePCM in the PVT system resulted in a notable decrease in panel temperature and a 25.03% increase in electrical efficiency compared to the conventional PV system. The highest performance ratio and overall efficiency for PVTNePCM were 0.55 and 81.62%, respectively, at a flow rate of 0.013 kg/s. The energy payback periods of PVTNePCM, PVTPCM, and PVT setup were 4.7, 4.8 and 5.6 years, respectively. Additionally, a significant improvement in thermal efficiency were observed for PVTPCM and PVTNePCM systems compared to water-based PVT systems, due to the energy stored in the thermal energy storage material. ? 2024 Elsevier Ltd